2016
DOI: 10.18413/2409-0298-2016-2-1-3-8
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormonal Regulation of in Vitro Formation of Wheat Androgenic Structures

Abstract: Seldimirova O.A., Zaytsev D.Yu., Galin I.R., Kruglova N.N. AbstractThe phenomenon of androgenesis in vitro is widely used in biotechnological investigations of spring wheat. When solving the specific biotechnological problems it is important to know what Seldimirova O.A., Zaytsev D.Yu., Galin I.R., Kruglova N.N. Phytohormonal regulation of in vitro formation of wheat androgenic structures // Сетевой журнал «Научный результат». Серия «Физиология». -Т.2, №1(7), 2016. 4 Серия ФИЗИОЛОГИЯ PHISIOLOGY Serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Stress and hormones influence chromatin reorganisation, which is a consequence of reprogramming transcription, and translation profiles in cells [22] play a key role in microspore embryogenesis induction [23]. Activation of the reprogramming process should result in initiation of embryogenic program and not development of non-morphogenic calli or apoptosis of microspores [24]. Moreover, in microspore embryogenesis, stress treatment initiates a rearrangement of the cytoskeleton and re-localisation of the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress and hormones influence chromatin reorganisation, which is a consequence of reprogramming transcription, and translation profiles in cells [22] play a key role in microspore embryogenesis induction [23]. Activation of the reprogramming process should result in initiation of embryogenic program and not development of non-morphogenic calli or apoptosis of microspores [24]. Moreover, in microspore embryogenesis, stress treatment initiates a rearrangement of the cytoskeleton and re-localisation of the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Auxinic herbicide 2,4-D (2,4-dichlorophenoxyacetic acid) is the most widely applied microspore embryogenesis inducer [24,25]. According to literature, this synthetic hormone when added to an induction medium has auxin-like effects and in addition acts as a stress factor [26].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that endogenous phytohormones are released when plants are exposed to stress. The amount and type of these hormones determine the demand of cells for exogenous hormones provided in the substrate [30]. Additionally, it is necessary to remember that winter wheat is more tolerant of low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…The auxin herbicide 2,4-D is widely used as growth hormone to induce embryo-like structures (Przetakiewicz et al, 2003;Seldimirova et al, 2016). Previous studies showed that this synthetic hormone added to the induction medium behaved as a stress factor and had auxin-like effects (Fehér, 2005).…”
mentioning
confidence: 99%